Species Diversity and Distribution of Amphibians in Tangjiahe National Nature Reserve, China - Mingfu Li; Mei Xiao; Li Zhao; Yiming Wu; Long Jin; Chengzhi Yan; Wenbo Liao (Biology, 2025)
Mountain ecosystems offer valuable opportunities to study species distribution and diversity along altitudinal gradients, particularly for amphibians. This research examined amphibian species distribution, diversity, and conservation across an elevational gradient in the Tangjiahe National Nature Reserve, part of the Hengduan Mountains in southwestern China. A total of 25 amphibian species, encompassing 8 families and 2 orders, were documented, including three newly recorded species: Fejervarya kawamurai, Polypedates braueri, and Boulenophrys minor. Among these, eight species were designated as “threatened” under IUCN criteria and are listed on China’s Biodiversity Red List. Caijiaba exhibited the highest species diversity, whereas Shuichiping had the lowest. Fourteen species were found in terrestrial-farmland and aquatic-lotic habitats, which supported the greatest species richness. The distribution pattern along the altitudinal gradient showed peaks in species richness at 900–1100 m and 1900–2100 m elevation bands, with higher elevations displaying reduced richness. These findings highlighted the spatial characteristics of amphibian distribution and diversity across altitudinal ranges in the Tangjiahe National Nature Reserve and provide insights for formulating conservation policies and adaptive habitat management strategies.